Satisfaction at care of patients with thyroid cancer treated at the Nuclear Medicine Service of the Hospital Nacional Guillermo Almenara Irigoyen, 2018 - Chávez Arámbulo, Patricia (2019)
Objective: To determine the satisfaction at care of patients with thyroid cancer at the Nuclear Medicine Service of the Hospital Nacional Guillermo Almenara Irigoyen. Materials and methods: A non-experimental, descriptive, cross-sectional study was carried out with a study population consisting of 267 patients with thyroid cancer. The instrument was taken from the "Technical Guide for the Evaluation of Outpatients’ Satisfaction", approved by the Ministry of Health of Peru, and made up of two components (perceptions and expectations), five dimensions and 22 questions for each component, with methodological and operational validation. Results: The patients’ average age was 52.5 years and the female sex prevailed. Regarding patient dissatisfaction, the reliability dimension showed 86.09 %, the response capacity dimension 84.3 %, the safety dimension 78.4 %, the empathy dimension 79.7 %, and the tangible aspects dimension 82.2 %. Conclusions: The reliability dimension obtained the highest dissatisfaction score, while the safety dimension had the best satisfaction results. The final dissatisfaction score accounted for 81 %.